Catalyst engineering technology : fundamentals and applications - Beeckman, Jean W. L. (John Wiley & Sons, Inc., 2020)
"The book begins with a summary of particle forming techniques in the particle technology industry. It covers extrusion technology in more detail since extrusion is one of the workhorses for particle manufacture. This book then gives a comprehensive explanation of what governs the breakage of extruded materials, and what techniques are used to measure it. The breakage during impact aka collision is explained using basic laws of nature allowing readers to determine the handling severity of catalyst manufacturing equipment and the severity of entire plants. This information can then be used to improve on the architecture of existing plants and how to design grass-roots plants. It presents the fundamentals of the study of breakage by relating basic laws in different fields (mechanics and physics) and this leads to two novel dimensionless groups that govern breakage. These topics are then applied to R & D scale-up and manufacturing and shows how this approach is directly applicable. The last chapter of the book is dedicated on how to describe transport and chemical reaction in such particulates for of course their final use. A catalyst, in simplest terms, is a material which enhances the rate and selectivity of a chemical reaction. Catalysis is central to the chemical industry, as it is directly or involved in the production of almost all useful chemical products. By implication, it is central to any technically advanced society. From the manufacture of bulk and specialty chemicals, through the production of fuels by petroleum refining to the control of unwanted environmental degradation, catalyst have a pivotal role to play. In this book the authors, present the definitive account of industrial catalytic processes."-- Provided by publisher
Keywords: Catalysts.; Extrusion process.; Catalysts industry.; elektronické knihy; electronic books